Build and Standardize the Organizational Commitment Scale for the Administrative Authority of Iraqi Football Clubs - Mohsen Mohammed Hassan (Journal of Global Pharma Technology, 2018)
The weakness in the administrative aspects was reflected on the players in the stadium during the competitions and competitions, and this also reflected the ability of the effective leadership of the coach in the coordination of work and follow-up and direct supervision and organize the efforts of the players, which gave the impression of the lack of effectiveness, which extends to the level and the extent required for players, Failure to achieve team goals and success. Building and standardizing the organizational commitment scale for the administrative authority of Iraqi football clubs to recognize the organizational commitment of the administrative authority of Iraqi football clubs. The researchers used the descriptive approach in the survey method and the standard, because of the relevance and nature of the current study. The information and data of the research community were collected (280) administrative members distributed among the clubs of the first class football in Iraq. The sample of the research was randomly selected. The sample of the building of the scale was (127) administrative members. Through the results of the results, the researchers reached the following conclusions:The members of the administrative body of Iraqi football clubs have shown a good organizational level, which has increased their level of ambition in the administrative process. Members of the administrative body of Iraqi football clubs have shown their football at an average level of organization, increasing their level of ambition in the administrative process. Set three standard levels of members of the administrative body of Iraqi football clubs. The possibility of using the scale applied in the current research by the administrative authority to measure the level of organizational commitment to them. Conduct studies similar to all workers in the federations and youth centers to find out the practical and scientific situation of workers in this field.Keywords: Organizational Commitment, Administrative authority and football.